Fighting to thrive via plant growth regulators: green chemical strategies for drought stress tolerance - Raza, A.; Bhardwaj, S.; Rahman, M.A.; Garcia-Caparros, P.; Copeland, R.G.; Charagh, S.; Rivero, R.M.; Gopalakrishnan, S.; Corpas, F.J.; Siddique, K.H.M.; Hu, Z. (2024)
As global climate change intensifies, the occurrence and severity of various abiotic stresses will significantly threaten plant health and productivity. Drought stress (DS) is a formidable obstacle, disrupting normal plant functions through specific morphological, physiological, biochemical, and molecular mechanisms. Understanding how plants navigate DS is paramount to mitigating its adverse effects. In response to DS, plants synthesize or accumulate various plant growth regulators (PGRs), including phytohormones, neurotransmitters, gasotransmitters, and polyamines, which present promising sustainable green chemical strategies to adapt or tolerate stress conditions. These PGRs orchestrate crucial plant structure and function adjustments, activating defense systems and modulating cellular-level responses, transcript levels, transcription factors, metabolic genes, and stress-responsive candidate proteins. However, the efficacy of these molecules in mitigating DS depends on the plant species, applied PGR dose, treatment type, duration of DS exposure, and growth stages. Thus, exploring the integrated impact of PGRs on enhancing plant fitness and DS tolerance is crucial for global food security and sustainable agriculture. This review investigates plant responses to DS, explains the potential of exogenously applied diverse PGRs, dissects the complex chemistry among PGRs, and sheds light on omics approaches for harnessing the molecular basis of DS tolerance. This updated review delivers comprehensive mechanistic insights for leveraging various PGRs to enhance overall plant fitness under DS conditions.